PENYULUHAN PEMANFAATAN TEKNOLOGI INFORMASI GUNA MENDUKUNG PEMINJAMAN MODAL DI MASYARAKAT - Suraya -; Muhammad Sholeh (LPPM IST AKPRIND Yogyakarta, 2019)
Information technology is no different now like a reliable assistant, who can do many things in all human activities including economic activities. Many business units that utilize this information technology to develop their business. Information systems that were previously only used for communication purposes, showed great benefits in the business world both on a large scale and community scale such as UKM. The benefits of information technology in the business world are to assist processes and operations, make decisions, and form strategies to gain competitive advantage. In community service activities in the hamlet of Karet, Bantul Pleret has socialized an application that can be simulated in providing loans. With this socialization, it is expected that the community will better understand the use of information technology in carrying out economic activities.